Biological Wastewater Treatment and Resource Recovery 2017
DOI: 10.5772/67349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomonitoring of Microbial Communities in Tannery Wastewater Treatment Plant for the Removal of Retanning Chemicals

Abstract: This chapter focuses on culture-independent characterization and monitoring of microbial communities in tannery wastewater treatment system, with special reference to the degradation of two xenobiotic chemicals used in retanning processes. Molecular survey of a tannery wastewater treatment system through metagenomic and metatranscriptomic approaches revealed a diverse microbial community in each component of the treatment system with high gene copies for enzymes involved in the degradation of cyclic aromatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Clostridium species can move between planktonic (the virulent form, if pathogenic) and sessile (more antibiotic resistant) forms, as needed (Crowther et al, 2014). Future studies that assess methods to enhance the treatment performance for tannery wastewater treatment plants should use culture‐dependent and culture‐independent approaches to monitor the fate of Clostridium across the treatment process, and determine whether the observations made here and at the Modjo tannery (Desta et al., 2017) are consistent with tannery treatment systems more generally. Notably, spore‐forming strains of Clostridium are known to be resistant to conventional disinfection (e.g., Kenters et al, 2017; LeChevallier & Au, 2004), which suggests that implementing such disinfection practices will not reduce their presence in the tannery effluent.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Clostridium species can move between planktonic (the virulent form, if pathogenic) and sessile (more antibiotic resistant) forms, as needed (Crowther et al, 2014). Future studies that assess methods to enhance the treatment performance for tannery wastewater treatment plants should use culture‐dependent and culture‐independent approaches to monitor the fate of Clostridium across the treatment process, and determine whether the observations made here and at the Modjo tannery (Desta et al., 2017) are consistent with tannery treatment systems more generally. Notably, spore‐forming strains of Clostridium are known to be resistant to conventional disinfection (e.g., Kenters et al, 2017; LeChevallier & Au, 2004), which suggests that implementing such disinfection practices will not reduce their presence in the tannery effluent.…”
Section: Resultsmentioning
confidence: 92%
“…The total chromium concentration (13–37 mg/L) was similar or lower than these other studies (27–68 mg/L). Tannery wastewaters are highly variable (Gutterres et al., 2015), likely due to the type of leather tanning activity (chrome or vegetable‐based), the amount of hair, the cleanliness of hides and skins collected from different regions, and the complexity of the leather making process itself (Desta, Nzioki, Maina, & Stomeo, 2017; Saxena, Chandra, & Bharagava, 2016). Indeed, in our study we saw raw COD and ammonia‐N concentrations that were higher and total chromium concentrations lower in the G2 sample than G1, possibly reflecting different input stocks being processed by the tannery at the time of sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Functional profiling of microbial communities allows the correlation of microbial phylogeny to function and also reveals the specific microbial groups that are most affected and the key genes that are actively expressed in a particular environmental condition [167]. This has been explored in a prior study where the genes involved in the degradation of cyclic aromatic compounds were identified through gene profiling conducted on microbial communities in tannery WWTP [180]. A comparative metatranscriptomics has also been conducted on WWTP to gain a deeper understanding of the functional and taxonomic attributes of the WWTP communities [181][182][183].…”
Section: Advanced Gene Expression Profiling For Wastewater and Aquatic System Monitoring Using Metatranscriptomics Approachmentioning
confidence: 99%
“…The leather tanning industry is one of the top water-consuming industrial enterprises nowadays. About 35-56 m 3 of water is used in a tannery industry to process per ton of raw hides or skins [1][2][3]. During the tanning process, aqueous solutions of different chemicals are used.…”
Section: Introductionmentioning
confidence: 99%